Preparation and Characterization of azo-Schiff-2- naphthol derivative complexes with metal ions (Open Herald: Periodical of Methodical Research, 2026)
The research included the preparation and identification of many of ligand with complexes of positively charged, copper, nickel, cobalt and zinc ions with a homocyclic azo-azomethene ligands 1-((E)-4-1-((Z)-1-((4-hydroxyphenyl)diazanyl)imino)phenyl)diazenyl)naphthalene-2-ol (Z1) and two organic ligands, (Z2= Ortho amino phenol) and(Z3= anthranilic acid). The outcome showed that the ligand and minerals mixture have the ratio (metal: ligand: ligand) (1:1:1). The stereoscopic shapes of the ligand mixture complexes were suggested using the results of ultraviolet-visible spectra, as well as the outcome of the susceptibility of magnetic and electrical conductivity measurements of the prepared chelate complexes. The shapes were tetrahedral of the ligand mixture complexes were proposed for the cobalt (II) and zinc (II) ions, and shapes was planar square for the nickel (II) complexes. Copper (II)